2014 IEEE Symposium on Computers and Communications (ISCC) 2014
DOI: 10.1109/iscc.2014.6912499
|View full text |Cite
|
Sign up to set email alerts
|

IEEE 802.11aa intra-AC prioritization - A new method of increasing the granularity of traffic prioritization in WLANs

Abstract: Audio-video streaming in Wi-Fi (IEEE 802.11) wireless local area networks (WLANs) has recently attracted a lot of attention. In order to increase the granularity of traffic prioritization and quality of service (QoS) support defined by EDCA, intra-access category prioritization has recently been introduced in the IEEE 802.11aa amendment. In this paper, we present novel results which show how the new mechanism impacts the performance of an access point (AP). Additionally, we propose a wireless credit-based shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Simulation results show that DEMS queuing outperforms traditional scheduling with FIFO queues. The most important advantages of DEMS queuing, in comparison to the traditional scheduling with FIFO queues, are the following: improved throughput and decreased queuing delay (mostly for high priority ACs) because of better channel usage; increased probability of transmission of time-critical traffic (e.g., video streaming) to end users, which could be advantageous, e.g., in cellular data offloading scenarios; decreased competition between frames destined to different users with parallel processing replacing the traditional FIFO approach; extendibility: the EDCA scheduling part can easily be replaced by, e.g, the 802.11aa intra-access category prioritization which provides better support for audio-video streaming [10,11]; increased flexibility: by introducing two queue levels (class and transmis- sion queues), one can either assign different ACs to the same user or the same AC to multiple users, therefore, more complex use cases can be considered. As future work we envision further enhancements of the proposed mechanism, e.g., the definition of the per-frame scheduler, and its comparison with alternate solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation results show that DEMS queuing outperforms traditional scheduling with FIFO queues. The most important advantages of DEMS queuing, in comparison to the traditional scheduling with FIFO queues, are the following: improved throughput and decreased queuing delay (mostly for high priority ACs) because of better channel usage; increased probability of transmission of time-critical traffic (e.g., video streaming) to end users, which could be advantageous, e.g., in cellular data offloading scenarios; decreased competition between frames destined to different users with parallel processing replacing the traditional FIFO approach; extendibility: the EDCA scheduling part can easily be replaced by, e.g, the 802.11aa intra-access category prioritization which provides better support for audio-video streaming [10,11]; increased flexibility: by introducing two queue levels (class and transmis- sion queues), one can either assign different ACs to the same user or the same AC to multiple users, therefore, more complex use cases can be considered. As future work we envision further enhancements of the proposed mechanism, e.g., the definition of the per-frame scheduler, and its comparison with alternate solutions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the general conclusions hold also for other standards, e.g., 802.11n/ac. 2 The intra-AC prioritization with presence of internal collisions was studied in our previous paper [11]. Different scenarios were considered in order to: select the best CBSA candidate (cf.…”
Section: Simulation Settingsmentioning
confidence: 99%
“…Other papers concentrated on reliable multicast mechanisms [6]- [8] and mathematical modeling of intra-AC prioritization [9], [10]. Additionally, in our previous paper [11] we have presented the general concept of intra-ac prioritization.…”
Section: Introductionmentioning
confidence: 99%
“…The IEEE 802.11 working group proposed IEEE 802.11e and IEEE 802.11aa for this purpose. Under these standards, various methods are proposed to guarantee QoS [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is difficult to adopt the proposed methods on a typical WLAN network. Furthermore, in [2], it is reported that throughput is not sufficient when IEEE 802.11e and IEEE 802.11ac are used in combination. Therefore, it is impossible for a public WLAN to guarantee QoS since many unspecified users exist.…”
Section: Introductionmentioning
confidence: 99%